# URGENT - Need help with figuring out how to solve equations by completing the square?

Solve the equation by completing the square.

-7x^2 - 10x + 3 = 0

x^2 - 3x - 15 = -5

x^2 - 17x = -10x - 6

Relevance
• norman
Lv 7

x^2 - 3x = 10

x^2 - 3x + (3/2)^2 = 10 + (3/2)^2

(x-(3/2)^2 = 49/4

x-(3/2) = +7/2 or -7/2

x = 3/2 + 7/2 = 5 or -2

x^2 - 7x = -6

x^2 - 7x + (7/2)^2 = -6 + (7/2)^2

(x-(7/2))^2 = -6 + 49/4

(x-(7/2)) ^2 = 25/4

x-(7/2) = +5/2 or -5/2

x = 7/2+5/2 = 6 or 7/2-5/2 = 1

• Anonymous
4 years ago

-7x^2 - 10x + 3 = 0, circulate huge type to easily right -7x^2 - 10x = -3, mult the two factors be -a million or 7x^2 +10x = 3, element-out the 7 or 7(x^2 +10/7 x) = 3, div by making use of seven (x^2 +10/7 x) = 3/7, complete sq. (x^2 +10/7 x + (10/14)^2 ) = 3/7 + (10/14)^2, notice we upload same element to the two factors (x +10/14)^2 = 3/7 + (10/14)^2, sparkling-up in simple terms right facet (x +10/14)^2 = 3/7 + (5/7)^2, sparkling-up some extra (x +10/14)^2 = 3/7 + 35/40 9 (x +10/14)^2 = 21/40 9 + 35/40 9 (x +10/14)^2 = fifty six/40 9, take sqrt, sparkling up left x +10/14 = + - sqrt(fifty six/40 9), sparkling-up left and in simple terms right x + 5/7 = + - sqrt(fifty six)/7 x = (- 5/7) + - sqrt(fifty six)/7 , notice there are 2 solutions.